Manisnya Cookies / Nur Iffa Hannani Hamdan - Hamdan, Nur Iffa Hannani (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
The product is Manisnya Cookies. Manisnya cookies are assorted shape sugar cookies. The name of the product 'Manisnya Cookies' reflects the sweetness of cookies. The product description is assorted shape cookies which comes in different shapes and flavours. The tagline is Sweet As You. The ingredients are flour, sugar, vanilla, soda bicarbonate, baking powder, food colouring, and butter. This product has been established in the market since March, 2016 Mrs, Annisa the founder of Manisnya Cookies feels that her business needs to be upgraded in terms of design and packaging, They decided to create the new design packaging and marketing. I chose this product because I believe that with knowledge in graphic design, I could help contribute to help uplift the new image of manisnya cookies. Manisnya Cookies.Sweet As You.